TRADITIONAL RETAIL AND MODERN RETAIL COMPETITION STRATEGY IN ISLAMIC BUSINESS ETHICS PERSPECTIVE - Wahidatul Maghfiroh; Susminingsih Susminingsih; Anis Wahdati; Ahmad Subiyadi (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to find out the level of traditional retail competition and strategies developed by traditional retail to remain resilient in modern business competition in an Islamic perspective. This study uses qualitative approach with phenomenological research type. The data is obtained from secondary data, namely data on the number of traditional retail and some modern retail in Wiradesa Subdistrict, Pekalongan Regency, Central Java. Research data obtained by interview techniques to business owners and consumers, observations and documentation. The population in this study was 8 modern retail (3 Alfamart, 5 Indomart), and 428 traditional retail (grocery stores and grocery stores) in Wiradesa Sub-district. Samples taken were 1 Alfamart in Gumawang Village, 1 Indomart in Gumawang Village, Adam's Shop in Gumawang Village, and Blue Shop in Kemplong Village, Pekalongan Regency. Data triangulation is used to maintain the validity of data. The study found that: (1) strategies developed by traditional retail are a) communication strategies as well as social relations with consumers as the implementation of Islamic values in the field of business services, b) cheaper pricing strategies, (2) modern retail applies a variety of promotions to attract consumers, (3) the business development system of both types of retail conducted does not deviate from Islamic business ethics.Keywords: traditional retail, modern retail, competitive strategy, Islamic business ethics.